Creating a framework for hospitality competencies to fufill the industry's need - Abdul Razak, Roshita; Mohd Shariff, Nurhazani; Zainol, Noor Azimin (SAVAP International, 2016)
This article examines the accommodation sector’s requirements on competencies for hospitality graduates.The main purpose of this study is to determine what the most desired competencies are and to come out with a framework for hospitality competency.16 representatives from the accommodation sector in Peninsular Malaysia participated in this study.A Delphi technique was used for data collection.Analyses discovered four important domains to be associated with the 69 hospitality competencies.37 competency items were categorized under Workplace Domain, 17 competency items under Personal Effectiveness Domain, 12 competency items under Management Domain and 3 competency items under Academic Domain.These findings provide important foundation for creating hospitality competency framework for educational institutions offering hospitality courses to close the gap on current competencies desired by the Malaysian hotel industry.